Relationship between magnetic properties and microstructure of ferrites during sintering in radiation and radiation-thermal conditions; Eurasian Physical Technical Journal; Vol. 18, No. 1 - Malyshev A. V. Andrei Vladimirovich; Lysenko E. N. Elena Nikolaevna; Sheveleva E. A. Elena Aleksandrovna; Surzhikova O. A. Olga Anatoljevna; Aryngazin A. K. Askar Kanapjevich (2021, 2021)
Title screen